(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In the context of digital transformation, the increasingly mature digital technology has accelerated the change of education and learning mode. As an important means of cultivating talents, personalized learning, empowered by digital technology, is highly compatible with the requirements of the strategy of “developing the country through science and education” and the goal of digital transformation of education. The study takes 1,651 documents included in the CNKI database from 1999 to 2024 as the research samples, and with the help of the visual analysis software CiteSpace, analyzes them in terms of keyword co-occurrence, core authors, and research institutes, and draws out the related knowledge maps. The study outlines the overall evolution of personalized learning under the collaboration of digital technology, and reveals the specific mechanism of digital technology to promote personalized learning experience. The study finds that personalized learning research in China has experienced three stages of slow development (1999-2009), rapid development (2010-2018), and stable development (2018-present). The process of digital technology for personalized learning experience mainly involves six aspects: educational concept, learning resource recommendation, openness and flexibility, personalization and customization, intelligent assessment and feedback, and outcome visualization. The latest frontiers of future research include the application of digital technologies such as artificial intelligence and smart education in personalized learning in language education.